Factor mobility and the distribution of economic activity in integrated economies : evidence and inplications - Bowen, Harry P.; Munundar, Haris; Viaene, Jean-Marie.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This study examines empirically factor mobility and distribution of economic activity under economic integration, with the result that the benchmark of the equal-share relationship holds strongly for US states and less so for EU countries, but does not hold for Developing Countries or the World. Recent research (Bowen, Munandar and Viaene, 2005) shows that for a country who is a member of a fully integrated economy, its shares of the integrated economy's total output and stocks of productive factors (i.e., physical and human capital) will be equal. They label this result the equal-share relationship. In this paper, we empirically examine for evidence of the equal-share relationship for alternative economic groups (i.e., US states, EU countries, Developing Countries and a World comprising 55 countries). Our findings indicate that the equal-share relationship holds strongly for US states, less so for EU countries, but does not hold for Developing Countries or the World.
Economic Papers